2022
DOI: 10.1007/s13199-022-00878-5
|View full text |Cite|
|
Sign up to set email alerts
|

A simple and low-cost technique to initiate single-spore cultures of arbuscular mycorrhizal fungi using a superabsorbent polymer

Abstract: Most species of arbuscular mycorrhizal fungi (AMF) are propagated with a host plant in a pot culture. However, the soil matrix makes it difficult to monitor the establishment and development of the symbiosis. In vitro culturing using Ri T-DNA transformed roots provides a clear medium and a sterile environment which offsets the constraints of the soil matrix. Nevertheless, the sterile conditions and the Ri T-DNA transformed roots provide very different growing conditions compared to a pot culture. Transparent s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The superabsorbent polymer (SAP)‐based autotrophic system was used for symbiotic cultures, (Paré et al ., 2022). The polymer was a poly(acrylamide‐co‐acrylic acid) potassium salt, and it is marketed as HORTA‐SORB® MD Granule by Horticultural Alliance (Sarasota, FL, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The superabsorbent polymer (SAP)‐based autotrophic system was used for symbiotic cultures, (Paré et al ., 2022). The polymer was a poly(acrylamide‐co‐acrylic acid) potassium salt, and it is marketed as HORTA‐SORB® MD Granule by Horticultural Alliance (Sarasota, FL, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The mother spores of R. cf fasciculatus together with their respective daughter spores were then transferred to microscope slides for observation by light microscopy. The superabsorbent polymer (SAP)-based autotrophic system was used for symbiotic cultures, (Par e et al, 2022). The polymer was a poly(acrylamide-co-acrylic acid) potassium salt, and it is marketed as HORTA-SORB ® MD Granule by Horticultural Alliance (Sarasota, FL, USA).…”
Section: Single-spore Culturesmentioning
confidence: 99%
“…Install nylon mesh filter membrane. 2022) 12 showed that the conditions on SAP were relatively neutral (6.7 to 7.4).…”
Section: Table Of Materialsmentioning
confidence: 98%
“…The modified twocompartment Petri dishes allow the cultivation of different AM fungal species. Paré et al12 have propagated seven different AMF species from six genera and three families.Modification of two-compartment Petri dishes is easily done with inexpensive tools. The cost and quantity of materials (vermiculite, SAP, Pasteur pipette, etc.)…”
mentioning
confidence: 99%
“…They use either Ri T-DNA root-transformed organs [266] placed into bioreactors comprising a solid support [267], airlift bioreactor [268] or small containers [269]. Whole plants can also be used with aerial organs outside a Petri dish while AMF and roots are in the Petri dish filled with a solid medium [270,271]. These in vitro techniques are performed in completely sterile conditions and should make it possible to produce large quantity, high quality and contaminant-free AMF inoculums [259,272].…”
Section: Amf Inoculum Productionmentioning
confidence: 99%